Tracing the historical foundations of infliximab in Crohn’s disease treatment: a cited reference analysis - Yeung, Andy Wai Kan (Frontiers in Pharmacology, 2024)
Introduction The use of infliximab to treat Crohn’s disease patients has been evaluated for decades. The current work aimed to identify the historical roots of this research topic. Methods The literature database Web of Science Core Collection was searched to identify relevant papers. Cited reference analysis on the identified literature set was performed using CRExplorer, a dedicated bibliometric software. The disruption index was computed with an automated routine described by Leydesdorff and Bornmann, which is freely available online. Based on data from citation count and reference list, the disruption index can range from −1 to +1, with −1 meaning a continuity from existing research and +1 meaning a disruption. Results This analysis successfully identified key references dealing with infliximab use on Crohn’s disease patients, such as the original report that introduced the Crohn’s Disease Activity Index (CDAI) in 1976, the first case series reporting a favourable outcome of infliximab infusion on 10 patients published in 1995, the first randomized controlled trial published in 1997, the ACCENT I and ACCENT II trials published in 1999 and 2002, and a couple of European consensus guidelines on the diagnosis and management of Crohn’s disease. Conclusion Cited reference analysis could reveal the historical origins of the use of infliximab in treating Crohn’s disease. Highly cited references included CDAI, important early clinical studies, and European consensus guidelines. The important cited references identified by the analysis provided solid foundation to support subsequent research.